The influence of price, service and product quality towards customer satisfaction of Honda Dealers Johor Bahru / Nur Amariah Md Ngaripin - Md Ngaripin, Nur Amariah (2012)
In a global scenario, customer satisfaction with a company’s products or services is often seen as the key to a company’s success and long-term competitiveness. Customer satisfaction also is an important strategic objective for retail and manufacturing industries. In order to survive and achieve profitability, organization needs to respond customer’s requirement to satisfy them. Although there are many factors which relate to customer satisfaction, but most of previous empirical research in this field tended to emphasize on only service quality, product quality and price which are critical relating to customer satisfaction. In order to achieve a quality service organization, commitment from employees and support from all levels of management is necessary. Therefore, it is important for managers who provide goods or services constantly to keep track of information about the company’s well-being as far as meeting this customer needs are concerned. Service companies are trying to find ways to improve and provide superior quality service to satisfy their customers. According to Wong and Sohal (2003), he mentioned that customer satisfaction is regarded as a primary determining factor of repeat shopping and purchasing behavior. The greater the degree to which a consumer experiences satisfaction with a retailer, the greater the probability the consumer will revisit the retailer.